Functionalized Base‐Stable Metal–Organic Frameworks for Selective CO2 Adsorption and Proton Conduction. Issue 22 (21st August 2017) - He, Tao; Zhang, Yong‐Zheng; Wu, Hao; Kong, Xiang‐Jing; Liu, Xiao‐Min; Xie, Lin‐Hua; Dou, Yibo; Li, Jian‐Rong
Abstract: Metal–organic frameworks (MOFs) have shown great potential for application in various fields, including CO2 capture and proton conduction. For promoting their practical applications, both optimization of a given property and enhancement of chemical stability are crucial. In this work, three base‐stable isostructural MOFs, [Ni8 (OH)4 (H2 O)2 (BDP‐X)6 ] (Ni–BDP‐X; H2 BDP=1, 4‐bis(4‐pyrazolyl)benzene, X=CHO, CN, COOH) with different functional groups, are designed, synthesized, and used in CO2 capture and proton conduction experiments. They possess face‐centered cubic topological structures with functional nanoscale cavities. Importantly, these MOFs are fairly stable to maintain their structures in boiling water and 4 M sodium hydroxide solution at room temperature. Functionalization endows them with tunable properties. In gas adsorption studies, these MOFs exhibit selective adsorption of CO2 over CH4 and N2, and in particular the introduction of COOH groups provides the highest selectivity. In addition, the COOH‐functionalized Ni–BDP exhibits a high proton conductivity of 2.22×10 −3 S cm −1 at 80 °C and approximately 97 % relative humidity. Abstract : Pores for thought : Three highly base‐stable isostructural MOFs, [Ni8 (OH)4 (H2 O)2 (BDP‐X)6 ] (Ni–BDP‐X; H2 BDP=1, 4‐bis(4‐pyrazolyl)benzene, X=CHO, CN, COOH), with pore surfaces lined by different functional groups are constructed, and used in CO2 capture and proton conduction experiments. The COOH‐functionalized MOF in particular exhibits selective adsorption of CO2 over CH4 or N2 and high proton conductivity.